2006
DOI: 10.1192/bjp.188.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime suicide rates in treated schizophrenia: 1875–1924 and 1994–1998 cohorts compared

Abstract: These findings point to an increase in suicide rates for patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
3
29
1
2
Order By: Relevance
“…for those needing depot preparations. 1,28 In line with these findings, the presence of akathisia, as well as parkinsonism, was associated with an increased risk of suicide among the subjects interviewed.…”
Section: Discussionsupporting
confidence: 67%
“…for those needing depot preparations. 1,28 In line with these findings, the presence of akathisia, as well as parkinsonism, was associated with an increased risk of suicide among the subjects interviewed.…”
Section: Discussionsupporting
confidence: 67%
“…42 The mortality rates where the death certificate mentioned schizophrenia were 8.2 per million for men and 7.1 per million for women. 20 65-74 14 suicide rate in psychotic patients 43 and the lifetime suicide attempt rate is around 22%. 11 A review of the literature between 1939 and 1998 estimated that the 20-year suicide rate in schizophrenia is between 14 and 22%.…”
Section: Mortality From Psychosismentioning
confidence: 99%
“…A recent study in Wales has shown that current rates of suicide among those with schizophrenia and other psychoses appear to be twentyfold higher than they were in the period 1875 to 1924. 22 Where the average life expectancy of the general population of the United States is 76 years (72 years for men and 80 years for women), the corresponding figure for the population with schizophrenia is 61 years (57 years for men and 65 years for women). In other words, compared with the general population, patients with schizophrenia have a 20% reduced life expectancy.…”
Section: Mortalitymentioning
confidence: 99%